The Dynamics of Women’s Empowerment as a Real-life Alternative Project for Women’s Engagement in the Traditional Coffee Industry : - Ulfah, Helmatun Fauza; Khairatunnisa, Khairatunnisa (Muadalah, 2023)
This study aims to explore the role of women in traditional coffee factories in remote areas of Indonesia. It employs the Power and representation analysis, phenomenological research, and “Representing Other” approach in Travel Literature to examine how people use a universal structure or essence to understand their experiences. It highlights the significance of women's involvement in the coffee industry, particularly those who have long been part of the field. The research specifically examines the contribution of women to the world of traditional coffee factories, using a case study of "Kopi Cap 3 Kunci" located in Barabai, Hulu Sungai Tengah, South Kalimantan. Its goal is to provide a comprehensive understanding of the role of women in the coffee industry and their contributions to traditional coffee practices. Furthermore, to identify the challenges faced by women in their participation of practices and explores strategies to promote gender equality and empower women in the coffee industry. The findings of this study have important implications for policy and practice, as they inform initiatives to enhance the participation and contributions of women in the coffee industry.